Comparison of "growth promoted" and "normally grown" dichorionic-diamniotic twins: A population-based study - Polona Pečlin; Luka Kovač; Nataša Tul; Ivan Verdenik; Andreja Trojner Bregar (Elsevier, 2022)
Objectives: Macrosomia in singleton pregnancies and associated risks have been well characterized. Less is known about the outcomes of macrosomic newborns in twin pregnancy.Objective of this study was to compare maternal characteristics and perinatal outcomes of ''growth promoted twins'' (twin pairs with a total twin birth weight above 90th percentile) to ''normally grown twins'' (twin pairs with a total twin birth weight between 50th and 90th percentile). Methods: We evaluated data (maternal characteristics and perinatal outcomes) of dichorionic-diamniotic twins born at 34 weeks of gestational age or later over a sixteen-year period (2002-2018) in two birth weight groups. We excluded twin pairs born before 34th week of gestation and discordant twin pairs. We used data from the Slovenian National Perinatal Information System.To define the percentiles, twin-specific growth curves have been used. Results: Our study population consisted of 390 twin pregnancies with a twin total birth weight over 90th percentile and 1618 pregnancies with a total twin birth weight between 50th and 90th percentile for gestational age. Women in ''growth promoted'' twin group were significantly taller, heavier and more often multiparous. There was a higher incidence of gestational diabetes (10.8% vs 7.3%, OR 1.53 95% CI 1.06 - 2.22), a lower rate of caesarean births (48.2% vs 53.9%, OR 0.80 CI 0.64 - 0.99) and lower rate of assisted reproduction (21.0% vs 27.1%, OR 0.71 CI 0.55 - 0.93) in women in ''growth promoted'' twin group. There were no statistically significant differences in neonatal outcomes in both groups. Conclusion: In contrast to macrosomia in singletons, macrosomia in twins does not appear to increase the risk for adverse perinatal outcomes.